Gold Nanoparticles Inhibit VEGF165-Induced Migration and Tube Formation of Endothelial Cells via the Akt Pathway. (1st June 2014) - Pan, Yunlong; Wu, Qing; Qin, Li; Cai, Jiye; Du, Bin
Abstract : The early stages of angiogenesis can be divided into three steps: endothelial cell proliferation, migration, and tube formation. Vascular endothelial growth factor (VEGF) is considered the most important proangiogenic factor; in particular, VEGF165 plays a critical role in angiogenesis. Here, we evaluated whether gold nanoparticles (AuNPs) could inhibit the VEGF165 -induced human umbilical vein endothelial cell (HUVEC) migration and tube formation. AuNPs and VEGF165 were coincubated overnight at 4°C, after which the effects on cell migration and tube formation were assessed. Cell migration was assessed using a modified wound-healing assay and a transwell chamber assay; tube formation was assessed using a capillary-like tube formation assay and a chick chorioallantoic membrane (CAM) assay. We additionally detected the cell surface morphology and ultrastructure using atomic force microscopy (AFM). Furthermore, Akt phosphorylation downstream of VEGFR-2/PI3K in HUVECs was determined in a Western blot analysis. Our study demonstrated that AuNPs significantly inhibited VEGF165 -induced HUVEC migration and tube formation by affecting the cell surface ultrastructure, cytoskeleton and might have inhibited angiogenesis via the Akt pathway.